2020
DOI: 10.1002/mmce.22142
|View full text |Cite
|
Sign up to set email alerts
|

Epsilon‐shaped circularly polarized strip and slot‐loaded ultra‐wideband antenna for Ku‐band and K‐band

Abstract: A compact epsilon‐shaped (ε) ultra‐wideband (UWB) antenna for dual‐wideband circularly polarized (CP) applications has been investigated in this article. It consists of a stepped stub loaded modified annular ring‐shaped radiator and modified CPW ground plane. The ground plane is loaded with two semicircular notches and a spiral‐shaped slot. The impedance bandwidth (IBW) is 97.02% (10.4‐30 GHz) along with an overall footprint of 20 × 20 mm2. The fractional axial ratio bandwidth (3‐dB ARBW) for two wide bands is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…For quad‐band CP structures, the IBW is less than the proposed structure. Although the proposed structure has less ARBW than, 9‐11,13,14 those structures do not exhibit quad‐CP bands. Also, it is to be noted that as number of CP bands increases to four, there is a trend of ARBW being narrow 15‐17 .…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…For quad‐band CP structures, the IBW is less than the proposed structure. Although the proposed structure has less ARBW than, 9‐11,13,14 those structures do not exhibit quad‐CP bands. Also, it is to be noted that as number of CP bands increases to four, there is a trend of ARBW being narrow 15‐17 .…”
Section: Resultsmentioning
confidence: 91%
“…A dual band CP antenna with wide impedance bandwidth (IBW) is presented in Reference 9 where CP is achieved by orthogonal orientation of metallic stubs and using the ground plane as a radiator and broadband is obtained by adding parasitic rectangular patches. An epsilon‐based stub loaded feedline with modified square slot antenna gives dual CP bands in a wide IBW region 10 . A tilted D shaped monopole radiator is also capable of having wide IBW with two CP bands 11 .…”
Section: Introductionmentioning
confidence: 99%
“…A quarter-wave substrate integrated waveguide (SIW) cavity antenna having two-stub and defected ground plane structure (DGS) structure to achieve enhanced dual CP electromagnetic (EM) wave along with enhanced CP bandwidth for Ku-band applications has been presented by Kumar et al 22 A multiband microstrip antenna for ultra-wideband (UWB) communication application has been reported by Tang et al 23 A compact CP antenna for C-band application has been proposed by Ullah et al 24 A modified ground plane with square ring slot wideband CP antenna for C-and Kuband application has been reported by Patil et al 25 Dey et al 26 proposed a compact CP patch antenna for industrial, scientific, and medical (ISM) band. A stepped stub loaded, compact epsilon-shaped, dual ultra-wideband CP antenna for Ku-and K-band application has been reported by Jaiverdhan et al 27 The creation of elliptical slot inside the patch gives the wide bandwidth, reported by Angelopoulos et al 28 Highly efficient, wideband, cavity backed, low-cost printed circuit board (PCB)-laminated antenna array for Ku band is presented by Awida et al 29 Wang et al 30 achieved an improved gain and wide bandwidth in a microstrip antenna by creating a U-slot inside the patch. Borji et al 31 reported a high-gain, good efficient, low-cost, PCB-laminated, wave guide-fed antenna array for Ku-band application.…”
Section: Introductionmentioning
confidence: 97%
“…The majority of printed-circuit UWB antenna designs are reported in the 3-10 GHz span, with very few designs persisting to cover higher frequencies such as the 3-30 GHz band, with promising applications in medical, air-bone intercept, radar, missile systems, and short-range tracking systems. The Ku band (12)(13)(14)(15)(16)(17)(18) is used for high resolution tracking and tracking the satellite within the bandwidths of approximately 12.87-14.43 GHz and the vehicular radar band (22)(23)(24)(25)(26)(27)(28)(29) [12]. As wireless system tools develop and use higher frequency ranges to provide higher data transfer, a UWB antenna with a frequency range far beyond the FCC-authorized band is required to monitor and enforce various standard compliances, such as EIRP, immunity tests, and interferences.…”
Section: Introductionmentioning
confidence: 99%